In vitro eye embryogenesis from induced pluripotent stem cells for ocular surface disease treatment - FuestMatthias; MehtaJodhbir S. (眼科学报, 2016)
In their letter to Nature , Hayashi et al . describe a new method for the generation of ocular surface epithelium-like cells by incubating human induced pluripotent stem cells (iPS) into four defined concentric zones mimicking the developing eye, which the authors named as self-formed ectodermal autonomous multi-zone (SEAM) (1). Different SEAM zones contained cells with characteristics of the ocular surface ectoderm, the lens, the neural retina and the retinal pigment epithelium. Isolated corneal surface-like cells successfully reinstated a corneal epithelium in a rabbit limbal stem cell deficiency (LSCD) model. The paper offers a new option for patients with LSCD.